Desarrollo sostenible del páramo peruano: estudio de caso de los páramos de Pacaipampa, Frías y Huancabamba, departamento de Piura, Perú - Sabogal-Dunin-Borkowski, Ana (2023)
The paramo is an ecosystem whose importance lies in the conservation and accumulation of water and carbon. Its deterioration has repercussions on the increase of emissions and reduces aquifer recharge. Despite this, this ecosystem faces significant pressure in Peru, especially due to overgrazing. The study reviews the state of the paramo and links ecological conservation to the organizational structure of communities in the Piura highlands. The study aims to provide elements for the development of a sustainable management of the paramo ecosystem in the Pacaipampa, Alto de Frías, and Huancabamba paramos, in the Piura department, Peru. It is concluded that the paramo is a human-influenced ecosystem that, despite facing strong livestock pressure, can achieve sustainable development for local communities by linking its conservation through proper grazing management with the rest of the Piura region, allowing for its preservation.